Supply Chain Management of Safe Vegetables from Residue Chemicals of Producers and Consumers - Supit Boonlab; Issara Siramaneerat; Pimnapat Bhumkittipich (International Journal of Supply Chain Management, 2019)
Supply chain management was the action that producer and consumer have done the process to safe vegetable from residue chemicals, i.e., how producer plant and clean before transfer, how consumer select and clean. Research aims were to investigate participation behavior of producers and consumers to vegetable residue chemicals before transfer to market and to propose a model examination. Quantitative method with 400 respondents through semi structured questionnaire who were producer and consumer vegetable. Structural equation model was used to analyze factors influence to vegetable washing treatment. The result findings revealed that demography (age and marriage status), attitude, and information awareness can predict vegetable consumption behavior. Attitude and information awareness identified strongest influence significance to predict vegetable consumption behavior while demography was a bit significance influence. Besides, pesticides were residue that harmful to humans for information awareness. Buying organic vegetables was worthwhile for attitude and a year previous received information and introduction to consume organic vegetables for information awareness. Some misunderstanding issues in knowledge for people were discussed while factors influence to producers and consumers for safe vegetable transportation about washing residue from producer to consumer indicated how good condition people were. Moreover, supply chain management will be discussed based on findings to guide private and government arranging any policy to encourage the right factor in the future.